Tissue‐engineering acellular scaffolds—The significant influence of physical and procedural decellularization factors. Issue 1 (29th November 2016) - Starnecker, F.; König, F.; Hagl, C.; Thierfelder, N.
Abstract: The importance of decellularized medical products has significantly increased during the last years. In this paper, we evaluated the effects of selected physical and procedural decellularization (DC) factors with the aim to systematically assess their influence on DC results. 72 porcine aortic walls (AW) were divided into three groups and exposed to a DC solution for 4 h and 8 h, either continuously or in repeated cycles. The AW were rocked (90bpm), whirled (10 l/min), sonicated (120W, 45 kHz) or exposed to a combination of these treatments, followed by 10 washing cycles. Defining successful DC as removal of nuclei while keeping an intact extracellular matrix (ECM), we equalized the efficiency to the penetration depth (PD), obtained by DAPI fluorescence and H&E staining. Additionally, we performed scanning electron microscopy (SEM), Pentachrome and Picrosirius‐Red staining. Results showed that significantly higher DC depths are achieved on outer compared to inner surfaces (61 ± 7%; p < 0.001). Furthermore, the PD showed a high time dependency for all samples. Compared to continuous rocking, we achieved a significant increase in the DC efficiency through cyclic treatments ( ∼ 43%), whirling ( ∼ 19%) and sonication ( ∼ 49%). The combined treatment supported these results. In all procedures, a skeletonized but intact Collagen fibrous network was obtained as confirmed by SEM analysis. In conclusion, we systematically identified essential factors to significantly enhance DC procedures. We highly recommend considering these factors in future DC protocols. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 153–162, 2018.